Factors Associated with Methicillin Resistant Staphylococcus aureus Carriage - Abdulrahman, Masood Abdulkareem; Issa Taher, Arazoo (Kurdistan Journal of Applied Research, 2019)
S. aureus is a common commensal of the skin and mucosal membranes of humans, with estimates of 20% (range from 12% to 30%) of healthy people are persistent S. aureus nasal carriers, 30% (range from 16% to 70%) are intermittent carriers, and 50% (range from 16% to 69%) are non-carriers. The aim of this article is to explore the factors associated with Methicillin Resistant Staphylococcus Aureus carriage among food handlers. Across sectional study was done to involve 200 persons who are handling foods in 40 restaurants in Duhok city in the study. Methicillin Resistant Staphylococcus Aureus was detect among 27% of studied population. Methicillin Resistant Staphylococcus Aureus carrier rate showed a significant association with skin and soft tissue infections, health facilities visits and certain jobs of food handlers. Age, duration of work in the restaurants, personal protective measures and antibiotic use showed no significant association with the prevalence of MRSA. Methicillin Resistant Staphylococcus Aureus carrier rate was higher among food handlers working in popular restaurants when compared to other restaurants. Ongoing screening of all persons who handled foods is crucial to detect and treat those are MRSA carrier as one of major public health issues